DEVELOPING TEAM ASSISTED INDIVIDUALIZATION INTERACTIVE LEARNING MEDIA FOR THE TECHNOLOGY OF INFORMATION AND COMMUNICATION SUBJECT WITH THE TOPIC OF GRAPHIC DESIGN FOR GRADE XII STUDENTS IN SMAN 1 SUKASADA IN THE ACADEMIC YEAR 2011/2012 - Ni Made Yunia Ardianti (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This study aimed at (1) designing and implementing the development of TAIbased interactive learning media for the technology of information andcommunication subject with the topic of graphic design for grade XII students ofSMAN 1 Sukasada; (2) knowing the students and teachers’ response towards thedevelopment of TAI based interactive learning media for the technology ofinformation and communication subject with the topic of graphic design.This study was in the form of Research and Development/ R&D with the designdeveloped by Dick and Carey. It involved the students from SMAN 1 SUKASADAin the academic year of 2011/2012. The data were taken from interview. The validityof TAI based learning media as well as students and teachers’ responses werecollected through questionnaire. The data were then analyzed descriptively.Waterfall model was used in the development of TAI based learning mediawhich was designed by using DFD (Data flow Diagram). It was also implemented byusing Adobe Dreamwaver CS3 software. The result of students’ response analysisshowed that 9% of the students gave extremely positive response, while 87% studentsgave positive response and 4% of the students gave less positive response. Therewere no students who gave negative or extremely response to it. The students’average score was 65, 78 points. It showed that the students’ response to thedevelopment of TAI based learning media was in the positive level. Meanwhile theresult of data analysis on the teachers’ response showed that 100% of the teachergave positive response to the development of the media.Key words: interactive learning media, cooperative, TAI (team assistedindividualization)